2021
DOI: 10.1038/s41598-020-79139-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Hsp90 levels in patients with systemic sclerosis and relation to lung and skin involvement: a cross-sectional and longitudinal study

Abstract: Our previous study demonstrated increased expression of Heat shock protein (Hsp) 90 in the skin of patients with systemic sclerosis (SSc). We aimed to evaluate plasma Hsp90 in SSc and characterize its association with SSc-related features. Ninety-two SSc patients and 92 age-/sex-matched healthy controls were recruited for the cross-sectional analysis. The longitudinal analysis comprised 30 patients with SSc associated interstitial lung disease (ILD) routinely treated with cyclophosphamide. Hsp90 was increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

79
1,213
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 5,840 publications
(1,298 citation statements)
references
References 41 publications
79
1,213
6
Order By: Relevance
“… 10 , 14–19 In addition to ACE2, CD147 protein has been identified as a co-receptor in host cells to enhance the ability of SARS-CoV-2 to enter human cells, and cause COVID-19 disease. 11 , 14 , 16 , 17 , 20 , 21 …”
Section: Overview Of Sars-cov-2 Entry Mechanismmentioning
confidence: 99%
“… 10 , 14–19 In addition to ACE2, CD147 protein has been identified as a co-receptor in host cells to enhance the ability of SARS-CoV-2 to enter human cells, and cause COVID-19 disease. 11 , 14 , 16 , 17 , 20 , 21 …”
Section: Overview Of Sars-cov-2 Entry Mechanismmentioning
confidence: 99%
“…the introduction of OCT angiography (OCTA), a modern technique for non-invasive imaging of retinal blood vessels in vivo, it has been demonstrated that retinal vessel density is significantly reduced in patients with AD, likely due to abnormal Aβ deposits that build up inside blood vessel walls [18][19][20][21]. Latest studies demonstrated significant correlations between retinal vessel density and cognitive function domains [22,23], apolipoprotein E genotype AD [24], and cerebral volumetric changes [25]. However, OCTA imaging has also provided evidence of microvascular impairment owing to reduced vessel density within the peripapillary area and the macula in POAG [26].…”
Section: Competing Interestsmentioning
confidence: 99%
“…This result is also coherent with our recently published data, which established that interfering with protein degradation by forming a proteolytic queue at ClpXP will increase tolerance levels dramatically ( Deter et al, 2019 ). Transcriptomic analysis of queuing-tolerant population showed upregulation of genes related to metabolism and energy ( Deter et al., 2021 ). However, other studies reported that ppGpp and ATP reduction are not essential for persistence ( Pontes and Groisman, 2019 ; Chowdhury et al., 2016 ; Bhaskar et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since persistence and tolerance are present in phylogenetically diversified bacterial species ( Wilmaerts et al., 2019b ; Meylan et al., 2018 ), it is feasible that an underlying genetic mechanism is conserved in evolutionarily related microorganisms, and the most likely candidates are essential genes or the disruption of crucial networks. In our recent work, we demonstrate that antibiotic tolerance in Escherichia coli may result from a whole-cell response and can occur through multiple pathways or networks, which may work simultaneously and cooperatively to survive against antibiotics ( Deter et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%